2005
DOI: 10.1128/jcm.43.9.4908-4910.2005
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Allergic Alveolitis (Hypersensitivity Pneumonitis) Caused by Sphingobacterium spiritivorum from the Water Reservoir of a Steam Iron

Abstract: A case of extrinsic allergic alveolitis (EAA) caused by Sphingobacterium spiritivorum is described. The symptoms were associated with the use of a steam iron. The water reservoir was heavily contaminated with S. spiritivorum (10 6 CFU ml ؊1 ). This is the first report of S. spiritivorum as a causative agent of EAA. CASE REPORTA 34-year-old woman presented with a dry cough, thorax constriction, and overall weakness. During the preceding 5 months, she had experienced these dry cough episodes twice a week. On exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
(12 reference statements)
1
9
0
1
Order By: Relevance
“…Sequencing 16S rRNA genes PCR-amplified from 416 single-cell MDA reactions, we found 18 candidate commensal and potentially pathogenic species that were selected for 454 shallow sequencing. Initial read mapping and de novo assembly of the low-coverage 454 sequence data confirmed that we had obtained genomic sequences for the pathogen Streptococcus pneumoniae as well as bacterial species highly similar to and those reported to be potentially pathogenic, including Sphingobacterium spiritivorum (Tronel et al 2003;Kampfer et al 2005), Leptotrichia buccalis (Hammann et al 1993;Hot et al 2008), as well as the host-associated oral bacteria, Streptococcus mitis and Veillonella parvula. Of particular note, we found three MDA products with sequences for the oral pathogen Porphyromonas gingivalis, which is a periodontal pathogen involved in periodontal bone loss that has also been linked to progression of atherosclerotic disease (Pussinen et al 2007;Yilmaz 2008).…”
supporting
confidence: 67%
“…Sequencing 16S rRNA genes PCR-amplified from 416 single-cell MDA reactions, we found 18 candidate commensal and potentially pathogenic species that were selected for 454 shallow sequencing. Initial read mapping and de novo assembly of the low-coverage 454 sequence data confirmed that we had obtained genomic sequences for the pathogen Streptococcus pneumoniae as well as bacterial species highly similar to and those reported to be potentially pathogenic, including Sphingobacterium spiritivorum (Tronel et al 2003;Kampfer et al 2005), Leptotrichia buccalis (Hammann et al 1993;Hot et al 2008), as well as the host-associated oral bacteria, Streptococcus mitis and Veillonella parvula. Of particular note, we found three MDA products with sequences for the oral pathogen Porphyromonas gingivalis, which is a periodontal pathogen involved in periodontal bone loss that has also been linked to progression of atherosclerotic disease (Pussinen et al 2007;Yilmaz 2008).…”
supporting
confidence: 67%
“…The most common clinical isolates of S. spiritivorum have been from blood, urine and respiratory secretions 4 5 . S. spiritivorum has been associated with causing respiratory tract infections in patients with cystic fibrosis,5 cellulitis and sepsis,6 bacteraemia7 and hypersensitivity pneumonitis (extrinsic allergic alveolitis) 8. Most reported patients have had an immunocompromised state or multiple medical comorbidities 9…”
Section: Discussionmentioning
confidence: 99%
“…To date, 7 cases of S. multivorum infection have been reported worldwide in relation to septicemia [5, 18-20], peritonitis [21], respiratory tract infection [22], and necrotizing fasciitis [23]. Only 3 cases of S. spiritivorum infection have been reported worldwide [24-26]. The present case and previously reported cases are compared in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Tronel et al [25] reported a case of S. spiritivorum bacteremia. In 2005, Kronel et al [26] reported a case of cellulitis-associated sepsis caused by S. spiritivorum from the water reservoir of a steam iron.…”
Section: Discussionmentioning
confidence: 99%